Teletrabalho em uma Instituição de Ensino Público Federal: a Visão dos Efeitos a Partir dos Servidores . - Silva, Cleverson Leite da (2021)
Introduction: Teleworking became mandatory for many employees during the 2019 coronavirus outbreak (COVID-19). The virus has spread worldwide, with more than 14 million confirmed infections and more than 600,000 deaths on July 20, 2020 (Johns Hopkins CSSE, 2020). As an effective and necessary measure to control the COVID-19 pandemic, governments have determined policies for self-isolation and stay-at-home. The COVID-19 pandemic promoted teleworking as “an exogenous shock” (Aguilera et al., 2016), and it is possible that after the global health emergency many new teleworkers will continue to telework, at least part-time. Therefore, it became even more relevant to explore the theoretical foundations combined with an empirical analysis of telework to provide insights for the future development of telework. The problem: “In the view of public servants of a federal public education institution, what is the relationship between the effects (convergent and divergent) of teleworking, in welcoming and compromising productivity by teleworkers”? Many researchers have been studying the characteristics and effects of Telework, (Drucker and Khattak, 2000; Popuri and Bhat, 2003; Sener and Bhat, 2011; Singh et al., 2013). These studies confirmed that telework is strongly influenced by job characteristics, which can deprive employees of telework options, especially for manual workers and workers (Asgari et al., 2014; Sener and Bhat, 2011; Singh et al., 2013; Walls et al., 2007). The main objective: Identify the effects of teleworking in a federal public education institution in the view of servers, in order to correlate them with the level of reception to teleworking and the productivity of teleworkers. In theoretical terms, the research was supported by theories on the current technicalsociological context, the impact of the contributions of computational tools for the wide use of remote work (telework). Moreover, to support the analysis, a literature review (state of the art) on telework is carried out, conceptualizing it and detailing its effects in a federal public education institution. As for the methods and procedures, the research was outlined, in terms of its organizational strategy, where the scientific method used was the case study. The qualitative, diagnostic approach, configuring the research as an exploratory descriptive. In addition, to facilitate the qualitative characterization of the interviews, a questionnaire was applied to the respondent participants of the sample, employees who work in the administration of the institution, totaling 60 participants. Bibliographic research was also used as data collection - or research in secondary sources. The results, this dissertation project had the purpose of researching and identifying, in the view of servers, in a Federal Education Institution the effects of teleworking on its reception and the productivity of teleworkers. Methodologically, it was possible to answer the research question and reach the general objective. It was concluded that the effects of teleworking have an impact on the reception of teleworking and on the productivity of teleworkers, therefore it is necessary for teleworkers guidance from the sectors of social service, psychology and administration. On the other hand, in the analysis and discussion of the results, considering the view of the servers, some characteristics were observed that led the research to infer that remote work (teleworking) has a positive character requirement when it comes to productivity. It was also observed that information technology clearly causes changes in people's interactions with the environment, that is, changes occur between people and the institution, causing forms of adaptation to the new organizational dynamics (telework). From the results and conclusions, as a technological product, the project was elaborated: Technical report: “diagnosis and ways for the development of telework in a federal public education institution”, coming from this dissertation.